A collection system for dry solid residues from exhaled breath for analysis via atomic force microscopy. (9th January 2017) - Morozov, Victor N; Mikheev, Andrey Y
Abstract: Exhaled air contains sub-micron droplets of lung liquid, which potentially bear biomarkers of lung diseases. After dehydration they form dry residue particles (DRPs). As a first step in developing techniques to characterize individual DRPs, a new electrostatic collector was designed in which DRPs are charged within a unipolar corona charger, concentrated in a cone funnel, and deposited onto a limited area of a highly oriented pyrolytic graphite surface. The collector captures 80%–90% of DRPs at an optimal flow rate of 0.15 l min −1 . Atomic force microscopy (AFM) revealed flattened round particles 20–50 nm high, with notable protrusions at their surface suggestive of an inhomogeneous internal structure. Exposure to humid air resulted in the DRPs spreading over the surface, with a 50%–200% decrease in their heights and an increase in their lateral dimensions so that their volume decreased by only 10% ± 3%. Exposure to saturated chloroform vapor resulted in drainage of 10%–15% of the DRP volume (presumably lipids), forming collar-shaped rings around each particle but leaving the core size and structure unchanged. AFM measurements combined with laser counter measurements of the DRP concentrations were used to estimate that one liter of air exhaled by volunteers contained less than 100 pg of dry residue material.